Pemberdayaan Perempuan dalam Pencegahan Kanker Payudara di Puskesmas Bathin 2 Babeko Kabupaten Muaro Bungo Tahun 2022 - Cici Erila Sari; Ayu Mustika Handayani (Universitas Batanghari Jambi, 2023)
According to data from the World Health Organization (WHO), every year there are 7 million breast cancer sufferers in the world, and 5 million of them die. Breast cancer can be prevented by doing breast self-examination (BSE). Early detection can reduce mortality by 25-30%. The aim of the study was to determine women's empowerment in preventing breast cancer at the Bathin 2 Babeko Health Center, Muaro Bungo Regency. This research was a Quasy Experiment with a one group pre test and post test design. The location of the research was carried out at the Bathin 2 Babeko Health Center, Muaro Bungo Regency and this research was carried out in June 2022. The population in this study were all women of childbearing age who were in the working area of the Bathin 2 Babeko Health Center, Muaro Bungo Regency in 2021 as many as 316 people and the sample as many as 32 people. The data analysis used was univariate and bivariate analysis. The results showed that there was a significant effect before and after being given health education on respondents' knowledge about breast cancer prevention with a p-value of 0.000.